Molecular Engineering of Metal–Organic Frameworks as Efficient Electrochemical Catalysts for Water Oxidation - Liu, Yizhe; Li, Xintong; Zhang, Shoufeng; Wang, Zilong; Wang, Qi; He, Yonghe; Huang, Wei‐Hsiang; Sun, Qidi; Zhong, Xiaoyan; Hu, Jue; Guo, Xuyun; Lin, Qing; et al. (Advanced materials (Weinheim), 2023)
Metal–organic framework (MOF) solids with their variable functionalities are relevant for energy conversion technologies. However, the development of electroactive and stable MOFs for electrocatalysis still faces challenges. Here, a molecularly engineered MOF system featuring a 2D coordination network based on mercaptan–metal links (e.g., nickel, as for Ni(DMBD)‐MOF) is designed. The crystal structure is solved from microcrystals by a continuous‐rotation electron diffraction (cRED) technique. Computational results indicate a metallic electronic structure of Ni(DMBD)‐MOF due to the Ni–S coordination, highlighting the effective design of the thiol ligand for enhancing electroconductivity. Additionally, both experimental and theoretical studies indicate that (DMBD)‐MOF offers advantages in the electrocatalytic oxygen evolution reaction (OER) over non‐thiol (e.g., 1,4‐benzene dicarboxylic acid) analog (BDC)‐MOF, because it poses fewer energy barriers during the rate‐limiting *O intermediate formation step. Iron‐substituted NiFe(DMBD)‐MOF achieves a current density of 100 mA cm−2 at a small overpotential of 280 mV, indicating a new MOF platform for efficient OER catalysis. Molecular design and crystal engineering strategy are applied to construct thiol‐functionalized metal–organic frameworks (MOFs). This MOF platform is successfully decorated with nickel–sulfur links cooperating in the network. The prepared 2D MOF with enhanced electro‐conductivity and modified electronic structure demonstrates superior activity and robust stability toward the oxygen evolution reaction (OER), which paves the way to design MOFs at a molecular level.